Study of blood pressure in elementary school children at hill and seashore areas - Ani Ariani; T Erna Lisma; Iskandar Z Lubis; Rafita Ramayati; Rusdidjas Rusdidjas (Paediatrica Indonesiana, 2003)
Background Measurement of blood pressure is the most impor-tant tool for early detection of hypertension. There is an assump-tion that salt consumption of the population living at the seashoreis higher than that of those living on the hill area, and it would leadto higher blood pressure.Objective To find out whether there is any difference of bloodpressure between school-age children (6-13 years) living on thehill area (Brastagi subdistrict) and those living at the seashore area(Pantai Cermin sub district), North Sumatra.Methods A cross sectional study was conducted in Brastagi andPantai Cermin from September to October 1995. The subjects weretaken by a simple random sampling method. The blood pressurewas measured based on recommendation of The Second TaskForce on Blood Pressure Control in Children 1987.Results The means systolic pressure in boys of 6 years of age aswell as in girls of 6,8,12 and 13 years, and the means of diastolicpressure in girls of 6,7,8,11 years were higher in Pantai Cermin(p<0.05). Blood pressure had significant positive correlations(p<0.001) with age, weight and height in both areas. Overall, hy-pertension was found in 117 (11%) out of 1065 children, 11.6%among girls and 10.6% among boys. On the hill and at seashorearea, hypertension was found in 10.2% and 11.8% of children re-spectively, which was not statistically different (p>0.05).Conclusion In children, there was no significant difference be-tween the prevalence of hypertension on hill and seashore area